Current medical diagnosis & treatment 2024 - Papadakis, Maxine A.; McPhee, Stephen J.; Rabow, Michael W.; McQuaid, Kenneth R.; Gandhi, Monica (New York : McGraw-Hill, 2023)
"For more than six decades, CURRENT Medical Diagnosis & Treatment has been delivering the authoritative information students, residents, and clinicians need to build their medical knowledge, expertise, and confidence. Written by top experts in their fields, this unmatched guide is formatted in a way that enables readers to find the answers they need quickly and easily."--Provided by publisher
Includes bibliographical references and index
Keywords: Diagnosis -- Handbooks, manuals, etc; Therapeutics -- Handbooks, manuals, etc; Medicine -- Practice; Diagnosis; Therapeutics; Diagnosis; Therapeutics